The influence of sampling method on electrolyte concentrations, ph and buffer capacity of saliva in healthy individuals - Anđelski-Radičević Biljana; Milošević Maja; Dožić Ivan (Serbian Medical Society - Dental Section, Belgrade, 2016)
Introduction Saliva is a complex secretion, which plays an important role in maintenance of oral health. Analysis of saliva is fast, simple and non-invasive, and it is increasingly used as a biological sample for determination of various biochemical markers. The aim was to determine the influence of unstimulated saliva collection methods for measuring electrolytes concentration (sodium, potassium, calcium), pH and buffer capacity of saliva in healthy subjects. Material and methods 30 healthy subjects, males and females, aged 18 to 20 years, without oral and systemic diseases were included in the study. Unstimulated saliva samples were taken using a special tube (Salivette) and via direct spitting into the test tube. The concentrations of sodium and potassium were determined by flame emission photometry while spectrophotometry was used for calcium concentration. For the analysis of pH value of saliva pH-meter was used, while saliva buffer capacity was determined by titration with HCl (0.005 mol/L). Results The level of sodium in unstimulated saliva collected in test tubes was 8.43 ± 3.92 mmol/L and in special tubes 7.90 ± 4.33 mmol/L. Potassium level in unstimulated saliva collected in test tubes was 13.62 ± 0.99 mmol/L while in special tubes it was 13.54 ± 0.94 mmol/L. Mean values of sodium and potassium in unstimulated saliva didn't show statistically significant difference in their concentrations between the two methods of collecting saliva. In contrast to these electrolytes, calcium concentration was higher in the samples of saliva collected with special tubes (2.04 ± 1.05 mmol/L) compared to the samples taken by direct spitting into the test tube (1.38 ± 1.18 mmol/L) with statistically significant difference (p < 0.05). By analyzing the pH of unstimulated saliva it was found that the average pH value of saliva collected with special tubes was 7.05 ± 0.32, and after direct spitting into test tubes it was 7.35 ± 0.41. Buffer capacity of saliva in healthy subjects was lower after taking with special tubes (5.18 ± 0.74) compared to test tubes (5.36 ± 0.85), but without statistical difference. Conclusion Unstimulated saliva collecting methods using cotton pads (salivette) and direct spitting in the test tube did not affect the value of pH, buffer capacity, the concentrations of sodium and potassium, but affected the concentration of calcium in saliva from healthy subjects.